(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Batik is one of Indonesia’s original works of art that is continuously preserved in several regions in Indonesia. Several people working as batik crafters in Bojonegoro, East Java, Indonesia are under the assistance of Ademo. Based on the preliminary study conducted, most batik crafters had started to complain of pain in several parts of their body, which was considered due to work postures and nonergonomic work stations. Thus, this study was conducted to analyze the risk of Musculoskeletal Disorders using RULA and NBM. Materials and Methods: It was an observational study with cross sectional design. Data collection was conducted by conducted observation using RULA (Rapid Upper Limb Assessment), NBM (Nordic Body Map) and interviews with batik crafters in home industry. The population in this study was 42 batik crafters in a batik industry under the assistance of Ademos Bojonegoro. This study utilized total sampling technique by which the whole population were taken as the sample. Results: The results showed that 76.2% of batik crafters had a very high risk of MSDs on the right side of the body and on the left side of the body; 50% of batik crafters had a high risk of MSDs; and 50% had a very high risk of MSDs. The results of observations using NBM showed that 42.85% had a high risk of MSDs. Conclusion: This study concludes that all the batik crafters are in an emergency circumstance experiencing musculoskeletal disorders and need an ergonomic work station as soon as possible.